Wavefront aberrations caused by biomechanical effects after Small Incision Lenticule Extraction (SMILE) based on finite element analysis. Issue 7 (19th May 2023) - Song, Yinyu; Fang, Lihua; Liu, Qianwei; Gong, Jiahui; Guo, Binhui
Abstract: To examine wavefront aberrations induced by biomechanical effects after Small Incision Lenticule Extraction (SMILE) surgery. The three-dimensional (3D) finite element models of the human eye were established. By loading the intraocular pressure (IOP), the displacement of the anterior and posterior surface of the cornea was calculated. Then the displacement was converted into the wavefront aberrations by wave-surface fitting. The results showed that the induced wavefront aberrations were noticeable from biomechanical effects after SMILE surgery. The induced higher-order aberrations from the anterior corneal surface included spherical aberration, y-Trefoil, and x-Tetrafoil. Spherical aberration was positively correlated with corrected diopter (D), but x-Tetrafoil and y-Trefoil remained stable. The induced wavefront aberrations from the posterior corneal surface were smaller than those from the anterior corneal surface, and some of the aberrations compensated each other. With IOP increased, defocus and x-Tetrafoil from the anterior corneal surface increased, while y-Trefoil and spherical aberration decreased. The IOP only affected defocus from the posterior corneal surface. In addition, the incision size also had a distinct impact on primary x-astigmatism and x-Trefoil from the anterior corneal surface, and it had a smaller effect on the aberrations from the posterior corneal surface. Therefore, the biomechanical effects increased residual wavefront aberrations after SMILE refractive surgery.